The Effect of Inflation, Government Spending and Exports on Economic Growth in Indonesia - Susilawati, Susilawati; Wibowo, Muhammad Ghafur (Jurnal Magister Ekonomi Syariah, 2024)
This study examines the effect of inflation, government spending, and exports on Indonesia's economic growth in the period 1990–2023. The data used are time series data from the Central Bureau of Statistics (BPS) and the International Monetary Fund (IMF). The analysis method used is Vector Autoregression (VAR) with estimation through Eviews 13 software. The results of the analysis show that inflation has a negative but insignificant effect on economic growth. Government spending shows a significant positive effect, while exports have an insignificant negative impact. Overall, the dynamics of the three variables do not have a significant impact simultaneously on economic growth. However, the finding that government spending has a significant positive effect indicates the importance of optimizing state spending, especially if it is directed to strategic sectors that can increase national productivity. Negative inflation indicates the need for policies to maintain price stability. Although exports have not shown a strong influence, efforts to increase the competitiveness of export products remain relevant within the framework of long-term development. The originality of this study lies in the integration of three main macroeconomic variables in one VAR model to analyze their dynamic relationships. This approach provides a new contribution to the study of Indonesian macroeconomics and provides empirical evidence that can be used by policymakers in formulating sustainable economic growth strategies.